Early Adolescent Affect Predicts Later Life Outcomes. Issue 2 (14th April 2016) - Kansky, Jessica; Allen, Joseph P.; Diener, Ed
Abstract : Background: Subjective well‐being as a predictor for later behavior and health has highlighted its relationship to health, work performance, and social relationships. However, the majority of such studies neglect the developmental nature of well‐being in contributing to important changes across the transition to adulthood. Methods: To examine the potential role of subjective well‐being as a long‐term predictor of critical life outcomes, we examined indicators of positive and negative affect at age 14 as predictors of relationship, adjustment, self‐worth, and career outcomes a decade later at ages 23 to 25, controlling for family income and gender. We utilised multi‐informant methods including reports from the target participant, close friends, and romantic partners in a demographically diverse community sample of 184 participants. Results: Early adolescent positive affect predicted fewer relationship problems (less self‐reported and partner‐reported conflict, and greater friendship attachment as rated by close peers) and healthy adjustment to adulthood (lower levels of depression, anxiety, and loneliness). It also predicted positive work functioning (higher levels of career satisfaction and job competence) and increased self‐worth. Negative affect did not significantly predict any of these important life outcomes. In addition to predicting desirable mean levels of later outcomes, early positive affect predicted beneficial changes across time in many outcomes. Conclusions: The findings extend early research on the beneficial outcomes of subjective well‐being by having an earlier assessment of well‐being, including informant reports in measuring a large variety of outcome variables, and by extending the findings to a lower socioeconomic group of a diverse and younger sample. The results highlight the importance of considering positive affect as an important component of subjective well‐being distinct from negative affect.